MANAJEMEN PENDIDIKAN PENCAK SILAT DALAM RANGKA PENANAMAN NILAI BUDI PEKERTI LUHUR DI PERGURUAN PENCAK SILAT PERPI HARIMURTI YOGYAKARTA (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims: (1) To describe Planning martial arts education management PerPi Harimurti Yogyakarta (2) The organization of educational management and planting martial arts noble character value (3) The management of martial arts education in order to instill values of noble mind (4) Evaluation formation of noble character values in Universities Pencak Silat PerPi Harimurti Yogyakarta.This study used a qualitative descriptive research refers more phenomenological perspective and naturalistic. The data in this study were obtained from several sources that the Board of Elders or Swordsman, teachers / trainers, and students. The data were obtained by using the method of observation, documentation, and interviews. These data were analyzed using domain analysis and analysis of theme, namely, learning, analyze, interpret and draw conclusions from the phenomena that exist in the field.The results showed that (1) management planning has been quite good and has met the standard concept of planning (2) organizing the management of martial arts education in college Harimurti PerPi is good enough. The division of duties, responsibilities, and authority specified in the meeting (Elders, Council Swordsman and Master), Related to instill values PerPi Harimurti budipekerti noble college had tried to be implemented optimally (3) The chairman of the martial arts college PerPi Harimurti implement a democratic system in his leadership. Every decision is always discussed by PerPi Harimurti kadhang or residents. Planting Value noble mind in college PerPi Harimurti Pencak Silat is good, in view of the value in the input planting noble character in the syllabus and teaching rpp (4) relating to the evaluation, University of Pencak Silat PerPi Harimurti make improvements so that students or teachers (coaches ) can improve outcomes value.